Competency-Based Clinical Education: Validation of Teaching Demonstration Assessment Rubrics - Sahoo, Divya Ratna; Ragendran, Raghavi (Journal of Research in Vocational Education, 2025)
One of the most essential technical assistances that school heads can offer to the teachers in improving their attitude and performance is through clinical supervision. This study evaluated how the clinical supervision of school heads affect the teachers’ teaching demonstration performance of one hundred fifteen (115) elementary teachers in the five (5) schools within Tagoloan District, Division of Misamis Oriental, during the School Year 2024 - 2025. It also sought to identify any significant relationships between selected variables and determine which of the independent variable/s singly or in combination influence the teachers’ demonstration performance. The study employed descriptive correlational and causal research designs and utilized statistical tools like Mean and Standard Deviation, Pearson Product Moment Correlation Coefficient and Multiple Linear Regression. The study revealed that Pre-observation was highly implemented of all the clinical supervision. The teachers’ teaching demonstration was at Very Satisfactory Level. Clinical supervision showed weak to moderate positive correlation and with teachers’ teaching demonstration. Moreover, pre-observation and post-observation conducted by school heads influenced the teachers’ teaching demonstration. Thus, clinical supervision of school heads is important to improve teachers’ teaching practices. It can be recommended that school heads may continue the pre- and post-observation as clinical supervision, as they have been identified as significant predictors of teachers' performance.